Effect of macroscale formation of intraluminal thrombus on blood flow in abdominal aortic aneurysms. Issue 1 (2nd January 2016) - Raptis, Anastasios; Xenos, Michalis; Dimas, Stelios; Giannoukas, Athanasios; Labropoulos, Nicos; Bluestein, Danny; Matsagkas, Miltiadis I.
Abstract : A mathematical approach of blood flow within an abdominal aortic aneurysm (AAA) with intraluminal thrombus (ILT) is presented. The macroscale formation of ILT is modeled as a growing porous medium with variable porosity and permeability according to values proposed in the literature. The model outlines the effect of a porous ILT on blood flow in AAAs. The numerical solution is obtained by employing a structured computational mesh of an idealized fusiform AAA geometry and applying the Galerkin weighted residual method in generalized curvilinear coordinates. Results on velocity and pressure fields of independent cases with and without ILT are presented and discussed. The vortices that develop within the aneurysmal cavity are studied and visualized as ILT becomes more condensed. From a mechanistic point of view, the reduction of bulge pressure, as ILT is thickening, supports the observation that ILT could protect the AAA from a possible rupture. The model also predicts a relocation of the maximum pressure region toward the zone proximal to the neck of the aneurysm. However, other mechanisms, such as the gradual wall weakening that usually accompany AAA and ILT formation, which are not included in this study, may offset this effect.